Capacity Building for Mobile Coffee Micro, Small, Medium, Enterprises in Banyuwangi Regency - Sunarharum, Wenny Bekti; Nurcholis, Mochamad; Prananto, Yuniar Ponco; Satria, Dias (Journal of Innovation and Applied Technology, 2024)
The mobile coffee trend has become an innovation in marketing coffee products, especially in urban areas. Mobile coffee offers a more flexible and personalized way to reach consumers, in line with the increasing demand for coffee in Indonesia. This service is based on the need to increase the capacity of mobile coffee business actors in Banyuwangi Regency, which has great potential in the agricultural sector, especially coffee. A participatory approach was carried out in the form of training, technical guidance and assistance to mobile coffee business actors. This service includes training in post-harvest processing techniques, business management, and digital marketing strategies as well as technical guidance on coffee fruit production. Data was collected through interviews, and carrying out pre-tests and post-tests to measure the increase in understanding and skills of business actors. The research results show a significant increase in the knowledge and skills of mobile coffee entrepreneurs, especially in the aspects of post-harvest processing, production and marketing. The impact of this service is the creation of mobile coffee business actors who are more competent and able to compete in a wider market, as well as improving the quality of life through increasing income